A model-driven framework for developing android-based classic multiplayer 2D board games - Derakhshandi, Mohammad; Kolahdouz-Rahimi, Shekoufeh; Troya-Castilla, Javier; Lano, Kevin (Springer, 2021)
Mobile applications and game development are attractive fields in software engineering. Despite the advancement of programming languages and integrated development environments, there have always been many challenges for software and mobile game developers. Model-Driven Engineering (MDE) is a software engineering methodology that applies software modeling languages for modeling the problem domain. In this paradigm, the code is to be automatically generated from the models by applying different model transformations. Besides, manipulating models instead of code facilitates the discovery and resolution of errors due to the high level of abstraction. This study presents an approach and framework, called MAndroid, that generates Android-based classic multiplayer 2D board games in a fully automated fashion, relying on the concepts of MDE. Structural and behavioral dimensions of the game are first modeled in MAndroid. Models are then automatically transformed to code that can be run on any mobile phone and tablet running Android 4.4 or higher. In order to evaluate the proposed approach, three board games are fully implemented. Additionally, applicability, developer performance, simplicity and attractiveness of MAndroid are evaluated through a set of questionnaires. MAndroid is also evaluated technically by comparing it to other Android game-development frameworks. Results demonstrate the benefits of using MAndroid.
Keywords: Juegos de ordenador; Telefonía sin hilo; Ingeniería del software; Model Driven; Android; 2D Games; Board Games; Multiplayer Games